Inventory of ants (Hymenoptera: Formicidae) on decayed woods in mangrove forest area of Apar village, Pariaman, West Sumatera - Riani Zulisma fitri; Rijal Satria (Bioscience, 2022)
ABSTRACT. Ants are social insects that have a high diversity and wide distribution, including in mangrove forests. The existence of ant types in mangrove is influenced by human mobilization and ant migration. The ant migration naturally can occur through branches and twigs of decayed wood from mangrove trees that are drift on the ocean currents. The study to understand the distribution of ants across the islands can be done through a study of ant diversity on decayed woods in the mangrove area. This study aims to recognize the diversity of ants which is used decayed wood for nesting sites. This study was conducted in mangrove forest area of Apar Village, Pariaman city. Ants were collected by hand collecting method on every twigs, branched and decayed woods and then keep in vials filled by 70% ethanol. A total 11 species of ants that belong to 10 genera and 4 subfamilies were collected. Formicinae is the highest number of species that found in this study with 5 species, followed by Myrmicinae (3 spp.), Dolichoderinae (4 spp.), and Ponerinae (1 sp.).Keywords: Ants, Decayed woods, Diversity,  Inventory, Mangrove forestABSTRAK. Semut merupakan serangga sosial yang memiliki keanekaragaman yang tinggi dan penyebaran yang luas, termasuk di hutan mangrove. Keberadaan jenis semut di mangrove dipengaruhi oleh mobilisasi manusia dan migrasi semut. Migrasi semut secara alami dapat terjadi melalui dahan dan ranting kayu lapuk dari pohon mangrove yang hanyut terbawa arus laut. Kajian untuk memahami persebaran semut di seluruh pulau dapat dilakukan melalui studi keanekaragaman semut pada kayu lapuk di kawasan mangrove. Penelitian ini bertujuan untuk mengetahui keanekaragaman semut yang memanfaatkan kayu lapuk untuk tempat bersarang. Penelitian ini dilakukan di kawasan hutan mangrove Desa Apar Kota Pariaman. Semut dikumpulkan dengan metode pengumpulan tangan pada setiap ranting, kayu yang bercabang dan membusuk, kemudian disimpan dalam botol berisi etanol 70%. Sebanyak 11 spesies semut yang termasuk dalam 10 genera dan 4 sub famili dikumpulkan. Formicinae merupakan spesies terbanyak yang ditemukan dalam penelitian ini dengan 5 spesies, disusul Myrmicinae (3 spp.), Dolichoderinae (4 spp.), dan Ponerinae (1 sp.). Kata kunci: Semut, Kayu lapuk, Keanekaragaman, Inventarisasi, Hutan Mangrove